ESTUDO COMPARATIVO DA ATIVIDADE ANTIMICROBIANA DE EXTRATOS DE ALGUMAS ÁRVORES NATIVAS - Gonçalves, A. l. [UNESP]; Alves, A. [UNESP]; Menezes, H. [UNESP] (Instituto Biológico, 2022)
This study evaluated the antimicrobial activities (AA) of hydroalcoholic extracts obtained from 17 species of native Brazilian trees. The agar diffusion method was used against 10 different microorganisms isolated from inoculi obtained from clinically infected spots, for antibiosis assay purposes. Of the 170 tested carried out, 25% exhibited high AA, with Bixa orellana, Psidium guajava and Anacardium occidentale showing the most outstanding extract qualities. Exceptional AA was observed for Mimosa tenuiflora against Streptococcus pyogenes, Proteus mirabilis, Shigella sonnei, Staphylococcus aureus and coagulase-negative Staphylococcus spp. and Stryphnodendron adstringens, and for Eugenia uniflora extracts against Escherichia coli, Providencia spp., Streptococcus pyogenes, Proteus mirabilis, Shigella sonnei, Staphylococcus aureus and coagulase-negative Staphylococcus spp. Antibiosis essays with commercially available antibiotics were simultaneously conducted against the above-mentioned bacteria to compare with the AA potential of the trees extracts studied.

Este estudo avaliou as atividades antimicrobianas (AA) de extratos hidro-alcoólicos, obtidos de 17 espécies de árvores nativas do Brasil. Para os ensaios de antibiose foi utilizado o método da difusão em ágar, frente a 10 diferentes microrganismos, isolados de inóculos obtidos de focos de infecções clínicas. Dos 170 testes realizados, 25% mostraram alta AA, destacando-se extratos de Bixaorellana, Psidiumguajava e Anacardium occidentale. Excepcional AA foi observada em Mimosa tenuiflora contra Streptococcus pyogenes, Proteus mirabilis, Shigella sonnei, Staphylococcus aureus e Staphylococcus spp. coagulase-negativa, e os extratos de Stryphnodendron adstringens e Eugenia uniflora contra Escherichia coli, Providencia spp., Streptococcus pyogenes, Proteus mirabilis, Shigella sonnei, Staphylococcus aureus e Staphylococcus spp. coagulase-negativa. Ensaios de antibiose com antibióticos comerciais foram realizados contra estas bactérias, com a finalidade de se comparar o potencial de AA de extratos destas árvores.
COMPARATIVE STUDY ON ANTIMICROBIAL ACTIVITY OF SOME NATIVE TREE EXTRACTS
Keywords: Antimicrobial activity; medicinal plants; antibiosis; Atividade antimicrobiana; plantas medicinais; antibiose